2017
DOI: 10.1016/j.jimonfin.2017.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Monetary policy and covered interest parity in the post GFC period: Evidence from the Australian dollar and the NZ dollar

Abstract: Unlike the other major currencies, the Australian Dollar and the NZ dollar had lower interest rate than the US dollar on forward contract in the post GFC period. The purpose of this paper is to explore why this happened through estimating the covered interest parity (CIP) condition. In the analysis, we focus on a unique feature of Australia and New Zealand where short-term interest rates remained significantly positive even after the GFC. The paper first constructs a theoretical model where increased liquidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Australia's basis moved in the opposite directionit came to be relatively more positive. This supports the finding of Fukuda & Tanaka (2017) which document that a combination of financial instability and price instability stoked inflationary pressure in Australia. On the other hand, other advanced economies experienced a combination of financial instability and price instability of a deflationary type.…”
Section: The Cross-currency Basis Swap (Ccbs)supporting
confidence: 87%
“…Australia's basis moved in the opposite directionit came to be relatively more positive. This supports the finding of Fukuda & Tanaka (2017) which document that a combination of financial instability and price instability stoked inflationary pressure in Australia. On the other hand, other advanced economies experienced a combination of financial instability and price instability of a deflationary type.…”
Section: The Cross-currency Basis Swap (Ccbs)supporting
confidence: 87%
“…According to Covered Interest Parity that the differential in the rate of interest between foreign and local financial assets of the identical category is simply, equivalent to related forward premium of rate of exchange. In the recent past the findings related to the international finance literature favour the Interest Parity condition (Fukuda & Tanaka, 2017; Kim, Hoskisson, & Lee, 2015; Taylor, 1989). According to Uncovered Interest Parity apart from that, depreciation in the anticipated rate of nominal exchange rate is due to the differential in nominal rate of interest among countries in case of identical commodities.…”
Section: Model Specificationmentioning
confidence: 99%
“…Results are very similar, but tests showed that we cannot reject the presence of unit roots in the evolution of most series. Hence, we prefer to present regressions estimated on first differences.8 We do not include Australia and New Zealand in the baseline regressions since they consistently experience positive cross-currency dollar basis Fukuda and Tanaka (2017). focuses on the positive level of the cross-currency dollar basis and concludes that unique monetary policy features in Australia and New Zealand made deviations from the CIP condition distinct on the forward contract.…”
mentioning
confidence: 99%